KARYA SASTRA SEBAGAI DOKUMEN SOSIAL DALAM TRILOGI CERPEN PENEMBAK MISTERIUS KARYA SENO GUMIRA AJIDARMA: KAJIAN SOSIOLOGI SASTRA-OBJEKTIF - Suantoko, Suantoko (Universitas Tanjungpura, 2019)
The Seno Gumira Ajidarma short story collected in the Penembak Misterius trilogy is very interesting to read. In addition, as a social document, the collection of short stories can be identified a social setting that actually became a place of social events occurred, the social setting of the Penembak Misterius that occurred during the New Order era in the 1980s. More precisely the social setting created at the party meeting officials in a hotel, the shootings through the night, and the violence of the state apparatus. The social context referred to by Seno Gumira Ajidarma is a mysterious shooting incident known as